DESAIN WEBSITE PEMESANAN JASA PERAWATAN KECANTIKAN DAN PENJUALAN PRODUK KECANTIKAN PADA GONOVA BEAUTY CARE - Jordan Frankl Pasaribu; RinRin Meilani Salim; Zulpa Salsabila (STMIK Budi Darma, 2019)
Gonova Beauty Care is a beauty clinic that offers various types of beauty care services, consultations and beauty products, which was established on September 14, 2016. Where all transaction activities at the clinic still use the traditional process where customers must first come to the clinic. To help overcome the problem in Gonova Beauty Care, the author tries to analyze and design a new system using the system development methodology, namely the System Development Life Cycle (SDLC) method. The proposed new system is based on the website to manage transactions that occur at the clinic and can make it easier for customers to place an order. The website is designed to serve the transaction of sales of beauty products and ordering beauty services. The design of this system uses the Bootstrap application for input and output design.Keywords: Website, Gonova Beauty Care, Order Service, Selling Beauty Products